A Model of an Agricultural Household in a Multi-Crop Economy: The Case of Korea - Ahn, Choong Yong; Singh, Inderjit; Squire, Lyn (The Review of Economics and Statistics, 1981)
It is the purpose of this paper to describe one method of extending the empirical applicability of the theory of the farm-household to multi-crop economies by integrating the econometric and linear programming models already available in the literature. Section I introduces the subject. In Section II the theoretical model is presented. In Section III Korean data are used to assess the quantitative significance of the approach by calculating and comparing household response to changes in input and output prices for two different specifications of the models. First, the household is analyzed from the consumption side on the assumption that farm profits are exogenous; this corresponds to the standard approach in consumer demand theory. And second, results are presented for a model in which consumption and production responses are integrated in a theoretically consistent fashion, and farm profits are allowed to reflect production responses to price changes. The results from this and other studies that use an integrated approach to production and consumption decisions highlight the need to change perceptions concerning agricultural household response to economic incentives in developing countries and to revise the design of economic projects and policies accordingly.